Group dynamics in exercise and sport psychology - Beauchamp, Mark R. (Mark Robert) 1972-; Eys, Mark A. (Routledge, 2014)
"Can a better understanding of group dynamics raise individual and team athletic performance or improve the outcomes of exercise interventions Much human behaviour in sport and exercise settings is embedded within groups where individuals cognitions, emotions and behaviours influence and are influenced by other group members. Now in a fully revised, updated and expanded second edition, Group Dynamics in Exercise and Sport Psychology explores the unique psychological dynamics that emerge in sport and exercise groups. It provides a clear and thorough guide to contemporary theory research, and applied practice covering core themes and cutting-edge topics as well as highlighting directions for future research.The book is organised into five thematic sections:Part 1: The Self in GroupsPart 2: Leadership in GroupsPart 3: Group EnvironmentPart 4: Motivation in Groups Part 5: Socio-Environmental Issues in GroupsThis new edition includes seven completely new chapters, exploring important emerging issues such as social identity the family, co-ordination and shared knowledge within sport teams, the group as a vehicle for facilitating individual behavior change social support and emotion regulation peer leadership and cultural perspectives in relation to group dynamics.No other book on group dynamics in sport or exercise offers such a close examination of the evidence base and therefore Group Dynamics in Exercise and Sport Psychology is important reading for all students, researchersor practitioners working in sport or exercise psychology, kinesiology sport and exercise science sports coaching, or physical education"-- Provided by publisher.